Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The impact of social engineering on cybersecurity risks in banks in the city of Riyadh in the Kingdom of Saudi Arabia Mr. Abdullelah Saeed Al Mohayya, Ms. Arwa Ahmed Makeen 2. The impact of the university education and knowledge transfer index on the global competitiveness of the United Arab Emirates from the perspective of quality employees Dr. Shawk Hasan Mahdi 3. Evaluating the impact of artificial intelligence applications on accelerating the project life cycle and increasing its flexibility: A comparative study of agile and traditional management methodologies Dr. Anwar Mohammed Gismallah Mohammed 4. The role of automation in improving the performance of human resources: A field study on the employees of Al-Habib Real Estate Company Ms. Afrah Ahmed Mahdami 5. The financial sector in the Kingdom of Saudi Arabia’s Vision 2030: Evaluation and achievements Dr. Emad Adnan Matyori 6. Economic analysis of the provision of industrial and manufacturing services in the Kingdom of Saudi Arab 2024 Dr. Sadiq Ali Mubarak Al-Shuwaikhat, Dr. Haya Ibrahim Abdulrahman Al Tuwaym, Dr. Sara Saad Al-Dawsari 7. Measuring the impact of the economic balance goals on the economic growth of the Iraqi economy for the period (1990-2023) Asst-Prof. Sikna Jahya Faraj 8. The nexus between Public Investment Fund Sports Revenue and economic development in Saudi Arabia Ms. Furqan Mahfouz Ali Almdoudi, Dr. Somaiyah Fahad Alalmai